Sperm count and motility are quantitatively affected by functional polymorphism of classically related to neurotransmitters mood regulators HTR2A, MAOA and SLC18A. - Cortés-Rodríguez, Miriam; Reyes Palomares, Arturo; Lendinez, Ana; Ruiz-Galdón, Maximiliano; Reyes-Engel, Armando (Elsevier, 2018)
Spermatozoa and neurones share similar membrane characteristics and features. Associations of multiple polymorphisms traditionally related to neurotransmission were investigated. Infertile men were grouped into controls with normospermia (n = 182) and idiopathic infertile men with asthenozoospermia (n = 103), and analysed as a case-control study and as a quantitative association of each genotype. Ten neurotransmission-associated genetic variants were mapped by SNP analysis using quantitative polymerase chain reaction with TaqMan probes. Men with HTR2A rs6313 had a higher risk of asthenozoospermia (OR = 2.14; P = 0.04). MAOA rs3788862 G carriers displayed an increased risk of asthenozoospermia (OR = 2.29; P = 0.02). The SLC18A1 rs1390938 G allele was more frequent among such cases (0.75 versus 0.87; P < 0.01 and P < 0.01 for Armitage trend test); for SLC18A1 rs2270641 P = 0.02 (case-control frequency) and P = 0.01 (Armitage trend test). MAOA rs3788862 was correlated with sperm motility (Spearman ρ = 0.14; P = 0.02); SLC18A1 rs1390938 was correlated with sperm count and motility (Spearman ρ = 0.20; P < 0.01). Gene polymorphisms of HTR2A, MAOA and SLC18A1, related to neurotransmission, are individually associated with asthenozoospermia through variation in sperm count and motility, without detectable allelic or genotype interaction.
Keywords: Espermatozoides; Esterilidad masculina; Asthenozoospermia; Male infertility; Neurotransmission; Polymorphism